Nauja Lietuva - Nowa Litwa - New Lithuania. - Jablonskiene, Lolita; Jurenaite, Raminta; Malasauskas, Raimundas; Nowak, Maciej; Parulskis, Ernestas; Pipinyté, Zivile; R.G.; Rastauskas, Rolandas; Sabaseviciené, Daiva; Stankevicius, Evaldas; Trilupaityté, Skaidra; Trofimienkow, Michail; et al. (Gdansk : The Baltic Sea Cultural Center, 1996)
Jablonskis, Linas ; Rakauskaité, Eglé ; Stanikiené, Svajone ; Makarevicius, Gintaras ; Raila, Arturas ; Narkevicius, Deimantas ; Bastys, Darius ; Zungaila, Giedrius ; Ozarinskas, Valdas ; Ceponyte, Aida ; Liskevicius, Dainius ; Jankauskas, Donatas ; Sputis, Gintaras ; Gruodis, Karla ; Trimakas, Gintautas ; Bubelyté, Violeta ; Stanikas, Paulius ; Ludavicius, Eimantas ; Sarapova, Jurga ; Genceviciené, Jurga ; Straukaité, Sandra ; Parulskis, Liudas ; Misevicius, Saulius ; Bucas, Audrius ; Cukermanas, Markas ; Ozarinskas, Valdes ; Ceponyte, Aida
biografie
Engels
Contemporary Lithuanian Art Festival "New Lithuania", Gdansk, September-October, 1996
boek
Keywords: Litouwen